PANDANGAN AL-QUR'AN TERHADAP ISU KONSUMERISME MASYARAKAT DI ERA GLOBALISASI - Akbar, Muhammad Rivaldi; Hamidatul Munauwarah, Husnul; Eri Rahmawati, Febrika; Mahda, Mahda; Sa’adah, Maulidatus (Jurnal Ushuluddin, 2025)
The purpose of this study is to determine how the Qur'anic study views in responding to consumerism issues in society in the digital era; namely including the existence of a lifestyle in following trends, showing off wealth, wasteful lifestyles and others. The research method is a qualitative descriptive method with the type of research included in the Library Research research type. The data sources in this study are primary data, namely books and journals which directly discuss the problem being studied, namely a theoretical study of the Qur'anic view of consumerism issues in society in the era of globalization. The results of the analysis are that there is criticism of the Qur'an on consumerism issues that directly prohibit such behavior, such as QS. Al-Ma'idah verse 88, Al-A'raf verse 21, Al-Baqarah verses 34 and 219 and Al-Isra verse 29. The solutions presented by the Qur'an include consuming halal and good food, prioritizing the principle of benefit, not being wasteful and stingy and not boasting about wealth.